Identification of an industrial scale semi-autogenous grinding circuit for control purposes - Giddy, Mark Robert (My University, 2015)
Optimisation of the control of an autogenous grinding circuit requires a better understanding of system dynamics than exists at present. To this end extensive operating data were acquired on an industrial semi-autogenous milling circuit and a model was developed to explain the circuit responses to changes in input variables. This model represents the trends in the data fairly accurately and showed that: • When an excess o f slurry was present in Me load (i.e. more than the volume of the voids) a pool of slurry forms st the toe of the load. • The complexity of the power dependence on the variables describing the mill load defied dynamic modelling with toe limited knowledge avail- • The key parameters determining grinding efficiency vary constantly as the grinding environment is disturbed indicating a need for adaptive con- • The flow through the mili is adequately modelled by a single well mixed Itwasalso clear that maximisation of the power with respect to themass alone was insufficient, and that control of the feed dilution water rate is essential. Mill discharge slurry theology was studied eo gain an insight into conditions in the load. An energy balance using temperature measurements around th t mill discharge sump provided a very reliable estimate of the mill discharge density. This estimate was not successfully used for control although this potential should be exploited. Attempts to commission an on-line measurement of discharge slurry viscosity failed. Several theories and ideas were tested in a production environment subject to a multiplicity of disturbances and conclusive qualitative results were obtained. An improved understanding of milling circuit dynamics and a rationalisation of where controi can be improved has resulted from this work.
Keywords: Ball mills--Grinding media; Milling machines